2019
DOI: 10.3354/meps13008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in macrofaunal biological traits across estuarine gradients: implications for the coastal nutrient filter

Abstract: Benthic macrofaunal communities have a profound impact on organic matter turnover and nutrient cycling in marine sediments. Their activities are of particular importance in the coastal filter, where nutrients and organic matter from land are transformed and/or retained before reaching the open sea. The benthic fauna modify the coastal filter directly (through consumption, respiration, excretion and biomass production) and indirectly (through bioturbation). It is hard to experimentally quantify faunal contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 70 publications
(79 reference statements)
1
11
0
Order By: Relevance
“…Importantly, other studies have observed changes in diversity and composition of traits along environmental transects, for example, in the Laptev Sea, shallow and deep habitats were separated based on differing trait expression (Kokarev et al, 2017). Also along the Emilia-Romagna coastline, the trait expression of the community was different closer to the coastline compared to offshore (Paganelli et al, 2012) and similar results have been found in the Baltic Sea (Villnäs et al, 2019). In our case, the similarity within functional traits per habitat could reflect that the functional trait expression is often controlled by species abundance.…”
Section: Trait Composition In Different Habitatssupporting
confidence: 73%
See 1 more Smart Citation
“…Importantly, other studies have observed changes in diversity and composition of traits along environmental transects, for example, in the Laptev Sea, shallow and deep habitats were separated based on differing trait expression (Kokarev et al, 2017). Also along the Emilia-Romagna coastline, the trait expression of the community was different closer to the coastline compared to offshore (Paganelli et al, 2012) and similar results have been found in the Baltic Sea (Villnäs et al, 2019). In our case, the similarity within functional traits per habitat could reflect that the functional trait expression is often controlled by species abundance.…”
Section: Trait Composition In Different Habitatssupporting
confidence: 73%
“…The trait composition of benthic communities can help to understand community dynamics and their effects on ecosystem functions such as nutrient cycling, primary and secondary production, changes in sediment properties, and also the dynamics and stability of the ecosystem (Norkko et al, 2013;Goswami et al, 2017;Gammal et al, 2019). In recent years, many investigations have utilized a combination of taxonomic and functional trait diversity, which has developed our understanding of ecosystem function and supported efforts for better ecosystem management and conservation (Bremner et al, 2003;Rodil et al, 2013;Villnäs et al, 2019). Many studies on species diversity of macrofaunal communities in mangrove ecosystems have been conducted globally (Morrisey et al, 2003;Pravinkumar et al, 2013;Al-Khayat et al, 2019;Vahidi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This further suggests that the role of vegetation for nutrient filtering in the coastal zone can vary extensively depending on the local environmental gradients, dominating species communities and biological trait composition of the occurring species. Benthic communities in inner coastal areas, more prone to eutrophication, express biological traits (short life span, high metabolism and elemental content per individual) that enhance turnover rates of carbon and nutrients (Villnäs et al 2019). In contrast, outer coastal areas, which are deeper and less-nutrient enriched, are dominated by large, long-lived and deep-burrowing species, likely to have a more prominent role for nutrient retention and removal from the coastal filter (Fig.…”
Section: Biological Effects On Biogeochemistrymentioning
confidence: 99%
“…Animals play an important role in mediating carbon and nutrient cycles, as they store these elements in their body tissues and recycle them via feeding, excretion, egestion, and remineralization (Vanni 2002; Allgeier et al 2017; Atkinson et al 2017). Faunal tissue often contains higher concentrations of carbon and nutrients compared to the surrounding environment (Sterner and Elser 2002) and hence animal biomass may function as a significant temporal carbon and nutrient pool, which is particularly stable in long‐living species (Griffiths 2006; Villnäs et al 2019). Theoretically, consumers regulate their inner elemental content and keep their body composition stable despite imbalances in nutrient availability, a concept referred to as homeostasis (Sterner and Elser 2002; Persson et al 2010).…”
mentioning
confidence: 99%